High performance concrete using bottom ash as fine aggregate - Purushothaman, M.; Senthamarai, Rm. (Journal of Structural Engineering, 2024)
This paper presents the experimental investigation on the effective use of bottom ash obtained from thermal power station as a replacement of fine aggregates and silica fume as a replacement of cement on the properties of High performance concrete (HPC). A preliminary study was made to determine the isolated effect and its optimum percentage of silica fume and bottom ash for making high performance concrete. With this preliminary data, further study was carried out on HPC. Totally 10 mixes were prepared for this tests. Out of which five were HPC mixes and five were Conventional Concrete (CC) mixes. HPC was prepared for various cement contents ranging from 300 kg/m³ to 500 kg/ m³ by replacing 10% of the volume of the cement by silica fume and 40% of the volume of the fine aggregate by bottom ash. The concrete mixes were evaluated for compressive, tensile and flexural strengths at 28 days and to compare them with those of CC mixes prepared for various cement contents ranging from 300 kg/m³ to 500 kg/m³. The investigations revealed that the combined use of industrial wastes silica fume and bottom ash improved the mechanical properties of high performance concrete which is otherwise hazardous to the environment and thus these two materials may be used as a partial replacement material in concrete making.